Connexin23 deletion does not affect lens transparency. (May 2016) - Berthoud, Viviana M.; Minogue, Peter J.; Snabb, Joseph I.; Dzhashiashvili, Yulia; Novak, Layne A.; Zoltoski, Rebecca K.; Popko, Brian; Beyer, Eric C.
Abstract: While connexin46 (Cx46) and connexin50 (Cx50) are crucial for maintaining lens transparency and growth, the contributions of a more recently identified lens fiber connexin, Cx23, are poorly understood. Therefore, we studied the consequences of absence of Cx23 in mouse lenses. Cx23-null mice were generated by homologous Cre recombination. Cx23 mRNA was abundantly expressed in wild type lenses, but not in Cx23-null lenses. The transparency and refractive properties of Cx23-null lenses were similar to wild type lenses when examined by darkfield microscopy. Neither the focusing ability nor the light scattering was altered in the Cx23-null lenses. While both Cx46 and Cx50 localized to appositional fiber cell membranes (as in wild type lenses), their levels were consistently (but not significantly) decreased in homozygous Cx23-null lenses. These results suggest that although Cx23 expression can influence the abundance of the co-expressed lens fiber connexins, heterozygous or homozygous expression of a Cx23-null allele does not alter lens transparency.